Supplementation of Diets With Spirulina Influences Immune and Gut Function in Dogs - Satyaraj, Ebenezer; Reynolds, Arleigh; Engler, Robyn; Labuda, Jeff; Sun, Peichuan (Frontiers in Nutrition, 2021)
Spirulina refers to two species of blue green algae (Arthrospira platensis, and A. maxima) consumed by humans as food for centuries. While, Spirulina has been shown to have immune enhancing properties in several animal and human studies, there are no systematic studies in dogs. The aim of this study was to evaluate the immunomodulatory effect of dietary supplementation with Spirulina in dogs. The study was conducted in two phases: Pre-test (8 wks) and Test (42 wks). 30 adult dogs (mean 2.9 yrs) were randomized into two groups and fed a nutritionally complete diet in the ‘Pre-test’ phase. At the end of ‘Pre-test’ phase all dogs received a rabies vaccine, and dogs in ‘test group’ were switched to diet supplemented with dried Arthrospira platensis (Spirulina). Response to rabies vaccine was evaluated by Rapid Flourescent Focus Inhibition Test (RFFIT). Gut immune response was assessed by measuring fecal IgA. Gut microbiota was evaluated by Temporal Temperature Gel Electrophoresis (TTGE) methodology. Repeated measures ANOVA was used to test for differences between groups and statistical significance considered to be p <0.05. Dogs fed diets supplemented with Spirulina demonstrated enhanced immune status by showing significantly higher vaccine response and higher levels of fecal IgA as compared to the control group. Supplementing diets with Spirulina also resulted in significantly increased gut microbiota stability in the test group. In conclusion, diets supplemented with Spirulina significantly enhanced immune response and gut health in dogs.